Architectonic, Dialogical Relations and Metalinguistic: the Basis of Bakhtinian Thought - Queiroz, Inti Anny (Linha D’Água, 2020)
This study is part of the theoretical reflection accomplished in the doctoral thesis developed until 2019 in which we used the Bakhtinian Architecthonic, that can be understood in two ways: as a theory systematizer, that encompasses the philosophical categories of understanding the world and as a comprehensive whole, organizer of meaning in a concrete statement and carried out in a responsible act. During the research, we realized the importance of the connection between architectonic and the concept of dialogical relations, created late in conjunction with the Metalinguistic discipline in the book about Dostoiévski from1963. Here, we seek to understand the construction of the Bakhtinian thought through the development of those concepts in the works of the Bakhtin Circle. We will analyze Mikhail Bakhtin theoretical texts as well as of other thinkers from the Circle such as Pável Medviédev and Valentin Volóchinov. In this analysis we seek to demonstrate the connection between architectonic, dialogical relations and the creation of the Metalinguistic discipline as the basis of Bakhtinian thought.